Composition of Total and Cell-Proliferating Bacterioplankton Community in Early Summer in the North Sea – Roseobacters Are the Most Active Component - Bakenhus, Insa; Dlugosch, Leon; Billerbeck, Sara; Giebel, Helge-Ansgar; Milke, Felix; Simon, Meinhard (Frontiers in Microbiology, 2017)
Heterotrophic bacterioplankton communities play an important role in organic matter processing in the oceans worldwide. In order to investigate the significance of distinct phylogenetic bacterial groups it is not only important to assess their quantitative abundance but also their growth dynamics in relation to the entire bacterioplankton. Therefore bacterial abundance, biomass production and the composition of the entire and cell-proliferating bacterioplankton community were assessed in North Sea surface waters between the German Bight and 58°N in early summer by applying catalyzed reporter deposition (CARD-FISH) and bromodeoxyuridine fluorescence in situ hybridization (BrdU-FISH). Bacteroidetes and the Roseobacter group dominated the cell-proliferating fraction with 10-55% and 8-31% of total BrdU-positive cells, respectively. While Bacteroidetes also showed high abundances in the total bacterial fraction, roseobacters constituted only 1-9% of all cells. Despite abundances of up to 55% of total bacterial cells, the SAR11 clade constituted <6% of BrdU-positive cells. Gammaproteobacteria accounted for 2-16% of the total and 2-13% of the cell-proliferating cells. Within the two most active groups, BrdU-positive cells made up 28% of Bacteroidetes as an overall mean and 36% of roseobacters. Estimated mean growth rates of Bacteroidetes and the Roseobacter group were 1.2 and 1.5 day-1, respectively, and much higher than bulk growth rates of the bacterioplankton whereas those of the SAR11 clade and Gammaproteobacteria were 0.04 and 0.21 day-1, respectively, and much lower than bulk growth rates. Only numbers of total and cell-proliferating roseobacters but not those of Bacteroidetes and the other groups were significantly correlated to chlorophyll fluorescence and bacterioplankton biomass production. The Roseobacter group, besides Bacteroidetes, appeared to be a major player in processing phytoplankton derived organic matter despite its low partitioning in the total bacterioplankton community.